Effectiveness of custom-made foot orthoses in patients with systemic lupus erythaematosus: protocol for a randomised controlled trial - María Reina-Bueno; María del Carmen Vázquez-Bautista; Inmaculada C Palomo-Toucedo; Gabriel Domínguez-Maldonado; José Manuel Castillo-López; Javier Ramos-Ortega; Pedro V Munuera-Martínez (BMJ Open)
Introduction Systemic lupus erythaematosus (SLE) is a chronic autoimmune disease of heterogeneous involvement. The disease may affect feet with a high prevalence of symptoms such as, for example, pain, forefoot and rearfoot deformities, and biomechanics dysfunctions. Custom-made foot orthoses (CMFO) have been previously reported to be effective in patients with other rheumatic diseases. However, as far as the authors know, there exist no studies about their effectiveness in SLE. This study aims at determining the effect of CMFO versus placebo flat cushioning insoles on pain, foot functionality, fatigue and quality of life in patients with SLE.Methods and analysis A randomised controlled trial would compare the effects of (1) CMFO and group B, which received a placebo, flat cushioning insoles, for 3 months. The main outcome measures are foot pain, foot functionality and foot-related disability. The secondary outcome measures are fatigue and quality of life.Ethics and dissemination The study has been approved by the Portal de Ética de la Investigación Biomédica de Andalucía ethical committee 1494-N-19. The results will be disseminated regardless of the magnitude or direction of effect.Trial registartion number Clinicaltrials.gov identifier NCT04098055.